How trust in a destination's risk regulation navigates outbound travel constraints on revisit intention post-COVID-19: segmenting insights from experienced Chinese tourists to Japan - Sun, Tao (2022)
How do tourists cope with outbound travel constraints post-COVID-19? This study explores the cognitive coping strategy of destination trust in risk regulation on abating outbound travel constraints and catalyzing revisit intention. Taking Japan as a destination, analysis of data collected from 556 experienced tourists from Mainland China uncovered four types of travel constraints: health concern constraint, structural constraint, geopolitical constraint, and disinterest. Only disinterest had a significant negative impact on revisit intention. Trust in the destination government significantly increased revisit intention and ameliorated all types of travel constraints. Trust in local residents and in the tourism industry relieved disinterest efficiently. Results of multigroup analysis revealed that compared with tourists who have visited Japan only once, tourists with two or more past visits had lower levels of outbound travel constraints, and the impact of disinterest on their revisit intention was significantly lower. They also showed higher trust in destination government and higher revisit intention. Moreover, health concern constraint was significantly reduced by trust in the tourism industry but to be significantly enhanced by trust in local residents among tourists with two or more past visits to Japan. The theoretical and practical implications for the recovery of tourism are discussed.